POLA PENGGUNAAN ANTIBIOTIK POST OPERASI PADA PASIEN YANG MENJALANI OPERASI GASTROINTESTINAL - Faridah, Imaniar Noor (Pharmaciana, 2013)
Gastrointestinal surgery is a surgery that has a high risk of the incidence of surgical wound infection (ILO).Surgical wound infection is the result of bacterial contamination when the operation happens. The purpose of thisstudy was to determine the pattern of post operative antibiotics usage in patients undergone gastrointestinalsurgery at PKU Muhammadiyah Hospital in Bantul. The result of this study was expected to be useful as a sourceof information on patterns of post operative antibiotics that used, as well as for a base for next studies. This studywas a descriptive non-experimental research that prospectively held at PKU Muhammadiyah Bantul YogyakartaHospital. Subjects for this study were all patients who had undergone gastrointestinal surgery, which hospitalizedat PKU Muhammadiyah Bantul Yogyakarta Hospital and met the inclusion criteria. As for the inclusion criteria inthis study i.e., patients who have undergone gastrointestinal surgery, patients undergo hospitalization, as well aspatients that use antibiotics for ILOs prevention. The data analyzed was data of patterns on antibiotics usage thatused to prevent ILO incident. Based on this study showed that the usage of the most widely used post operativeantibiotics is a combination of Ceftriaxon and Cefadroxil as many as 28 patients (47,46%). Intravenous antibioticsthat mostly used is Ceftriaxon as many as 43 patients (6,29%), whereas for the most of oral antibiotics isCefradoxil as many as 45 patients (76,27%).